PENGARUH FOTOGRAFI PRODUK SEPATU TERHADAP MINAT BELI MASYARAKAT DENGAN BLIND TEST - Lip Son; Deli , Deli (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Nowadays, online buying and selling transactions are increasing. In this case, product photography is very important. Good product photography can help attract consumer buying interest so that it can increase selling value. The purpose of this research is to find out which smartphone between Samsung and Apple can produce product photos that are more selling according to consumers, and to find out whether product photos affect people's buying interest in Batam City. In media design, the author utilizes the 4D method (Define, Design, Develop, Disseminate) in the development of Product Photos. In addition, the author also uses quantitative methods in which the distribution of data is distributed through Google Forms with a total of 385 data respondents accompanied by blind tests. The results of the study show that there is no significant comparison between Samsung smartphone products with a score of 4435 (54.2%) and Apple with a score of 3745 (45.2%) in producing more selling Product Photos. Then for the results of quantitative data analysis shows that Product Photos (significance value <0.01 in the t test) have an influence on people's Purchase Interest in Batam City. This influence can also be seen in the coefficient of determination, where Product Photos have an effect of 25.6% on the Buying Interest variable.